2012
DOI: 10.1016/b978-0-12-394596-9.00006-8
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models of Hemophilia

Abstract: The X-linked bleeding disorder hemophilia is caused by mutations in coagulation factor VIII (hemophilia A) or factor IX (hemophilia B). Unless prophylactic treatment is provided, patients with severe disease (less than 1% clotting activity) typically experience frequent spontaneous bleeds. Current treatment is largely based on intravenous infusion of recombinant or plasma-derived coagulation factor concentrate. More effective factor products are being developed. Moreover, gene therapies for sustained correctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 312 publications
(394 reference statements)
1
58
0
Order By: Relevance
“…[87][88][89] Characterization of FVIII-specific T-cell clones and lines, and their use in studies exploring cell-based immunotherapies to promote immune tolerance to FVIII, are suggesting novel approaches to reduce the incidence of inhibitors. 90,91 Animal models remain essential for mechanistic studies, 92 and preclinical examination has demonstrated potential immune-regulatory properties of Fc fusion proteins 93 and the possible mitigation of FVIII immunogenicity with the long-term persistence of circulating FVIII levels achieved by gene transfer either alone 94 or through the generation of T-regulatory cells. 95 …”
Section: Fviii Immunogenicity: Role For Vwfmentioning
confidence: 99%
“…[87][88][89] Characterization of FVIII-specific T-cell clones and lines, and their use in studies exploring cell-based immunotherapies to promote immune tolerance to FVIII, are suggesting novel approaches to reduce the incidence of inhibitors. 90,91 Animal models remain essential for mechanistic studies, 92 and preclinical examination has demonstrated potential immune-regulatory properties of Fc fusion proteins 93 and the possible mitigation of FVIII immunogenicity with the long-term persistence of circulating FVIII levels achieved by gene transfer either alone 94 or through the generation of T-regulatory cells. 95 …”
Section: Fviii Immunogenicity: Role For Vwfmentioning
confidence: 99%
“…In mouse models of various forms of hemophilia, no blood-filled lymphatic phenotypes have been reported. 52 These mice may have an intermediate phenotype, similar to the b 3 knockout mice, that is less obvious and escaped observation. However, lymphovenous hemostatic clots, which are small and function alongside valves, may simply not require thrombin activity to maintain blood/lymph separation.…”
Section: Mechanism Of Lymphovenous Clot Formationmentioning
confidence: 99%
“…4 Although there are currently no prophylactic protocols against inhibitor formation in patients, preclinical experiments in murine models of hemophilia A have provided proof of principle that preventive immune tolerance to FVIII can be established. [6][7][8][9][10][11] However, such protocols use genetic manipulation or immune suppressive drugs, raising safety concerns for translation to human treatment. In contrast, oral tolerance could be a more readily acceptable form of prophylactic tolerance induction and may be more readily tested in clinical trials.…”
Section: Introductionmentioning
confidence: 99%